MATERIALS ANALYSIS OF THE ENGLISH TEXTBOOK FOR THE TENTH GRADE STUDENTS IN INDONESIAN ELT CONTEXT - Setyawati, Yulia Fida; Fitriani, Ulwi Ajeng (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2023)
Selecting course books involves matching the material with course objectives and learners' needs. This study examined the “Bahasa Inggris SMA/MA/SMK/SMAK Kelas X Semester 1 English” textbook material using the McGrath, Cunningsworth, and National Education Standards Agency (BNSP) guidelines to develop an appropriate standard for a textbook evaluation. The blueprint of material evaluation consists of three major stages: pre-evaluation, evaluation, and post-evaluation. The level of compliance was divided into three categories: Yes (= 2 points), No (= 0 points), and Partly (1 point) for the purposes of tabulation and statistical data analysis. This simplified the discussion of the results by allowing a raw score of 0 to 2 for each of the categories examined. The research demonstrates that the textbook is appropriate for use as a teaching tool.  The results suggest that there are some highlights for the material evaluation. The provided activities ought to be well-rounded enough to grab the students' interests. Incorporating genuine texts from actual settings can offer students a true immersion in authentic spoken language, aiding them in effectively practicing language skills for real-life communication. It is important to include representations of gender equality and diverse ethnic groups to cater to the needs of students from various cultural and linguistic backgrounds.